Oral Glutamine Reduces Radiation Morbidity in Breast Conservation Surgery. Issue 5 (6th February 2013) - Rubio, Isabel; Suva, Larry J.; Todorova, Valentina; Bhattacharyya, Sudeepa; Kaufmann, Yihong; Maners, Anne; Smith, Maureen; Klimberg, V. Suzanne
Abstract : This study examined the effect of oral glutamine (Gln) on radiation injury in breast cancer patients undergoing radiation therapy. The radiation injury was evaluated using Radiation Therapy Oncology Group (RTOG) scales. Cosmesis was scored. Blood Gln and glutathione (GSH) levels were determined. Serum protein profiling was determined using surface‐enhanced laser desorption/ionization time‐of‐flight mass spectrometry (SELDI‐TOF MS). Patients receiving Gln scored significantly better in RTOG score than the patients receiving placebo. Cosmetic scores averaged excellent in the Gln group vs fair to good in the placebo group. Blood Gln and GSH levels were significantly higher in the Gln group vs the placebo group. Serum protein profiling with SELDI‐TOF MS identified a novel Gln‐responsive protein that showed amino acid similarity with myoglobin. These results suggest that Gln is an effective way to reduce radiation morbidity to breast cancer and is associated with the increased expression of a novel serum protein biomarker.